2008
DOI: 10.1016/j.jembe.2008.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Meiobenthic colonisation of soft sediments in arctic glacial Kongsfjorden (Svalbard)

Abstract: An in situ experiment on metazoan meiofauna colonisation and succession was carried out at Brandal (78°56.88′N, 11°51.63′E), situated in arctic glacial Kongsfjorden (Spitsbergen). 28 soft sediment containers were deployed at a depth of 20 m and sampled after a one-, two-and three-year immersion period. The main taxonomic groups, abundance of colonising meiofauna and sediment parameters are described and compared. Meiofauna communities at Brandal show the highest densities reported for inner Kongsfjorden to dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 41 publications
(53 reference statements)
0
12
1
Order By: Relevance
“…We observed that almost all sediment samples and 30-80% of each sediment surface was strongly populated by polychaetes and nematodes. Sediments of BRL at 20 m water depth, for example, showed abundances of 12,210-16,130 animals cm -2 dominated by nematodes and copepods (Veit-Köhler et al 2008). These dense communities of meiobenthic organisms as well as protozoa and bacteria probably strongly contributed to the measured high respiration rates.…”
Section: Discussionmentioning
confidence: 91%
“…We observed that almost all sediment samples and 30-80% of each sediment surface was strongly populated by polychaetes and nematodes. Sediments of BRL at 20 m water depth, for example, showed abundances of 12,210-16,130 animals cm -2 dominated by nematodes and copepods (Veit-Köhler et al 2008). These dense communities of meiobenthic organisms as well as protozoa and bacteria probably strongly contributed to the measured high respiration rates.…”
Section: Discussionmentioning
confidence: 91%
“…It is therefore possible that the occurrence of H. crispae at such high latitude could result from more favourable climatic conditions of the investigated area and warm waters of the West Spitsbergen Current, which transported this tardigrade species from more southern localities. In the previous surveys around the Svalbard archipelago, tardigrades were recorded only infrequently (in 2-7% of samples) and in very low numbers, with the maximum abundance ranging 0.8-2.5 specimens per 10 cm 2 (Szymelfenig et al 1995;Węsławski et al 1997;Włodarska-Kowalczuk et al 1999;Veit-Köhler et al 2008). Literature data indicate strong patchiness and variability in the Arctic intertidal meiofaunal abundance (e.g.…”
Section: Resultsmentioning
confidence: 97%
“…However, these studies focused mainly on macrofauna (see Węsławski et al 1993Węsławski et al , 2010 and cited literature therein) while largely ignoring meiofauna. Only very few studies (Szymelfenig et al 1995;Węsławski et al 1997;Włodarska-Kowalczuk et al 1999;Veit-Köhler et al 2008) examined meiofauna and reported tardigrades. Unfortunately, in these studies, tardigrades were considered only as a taxonomic group.…”
Section: Introductionmentioning
confidence: 99%
“…Our study was performed in Kongsfjorden (West Spitsbergen), an intensively studied area for which the physical conditions and biota are well documented (Hop et al 2002;Svendsen et al 2002;Wlodarska-Kowalczuk and Pearson 2004;Kaczmarek et al 2005;Kedra et al 2010;Voronkov et al 2013 and references therein). For the intertidal and shallow subtidal softbottom area in Kongsfjorden, it is generally assumed that occurrence and dynamics of species assemblages are predominantly triggered by abiotic factors such as ice scouring, meltwater discharge and a high sedimentation rate provoking the colonization of these areas with opportunistic, small macrofauna organisms (Ambrose and Leinaas 1988;Gutt 2001;Bick and Arlt 2005;Wlodarska-Kowalczuk et al 2005;Laudien et al 2007;Veit-Köhler et al 2008). These species are well adapted to natural disturbances, and their high reproduction rates enable them to quickly re-colonize disturbed areas (Bick and Arlt 2005;Conlan and Kvitek 2005;Kuklinski et al 2013).…”
Section: Introductionmentioning
confidence: 99%